PRODUCT DISTRIBUTION STRATEGY AND PERFORMANCE OF PHARMACEUTICAL COMPANIES IN SOUTH-WEST, NIGERIA - Brimah Aminu Nassir; Yusuf Ismaila; Nurudeen Bello Ahmed; Ajayi Olalekan Ezekiel (Sampoerna University, 2026)
Despite the increasing importance of strategic marketing practices in attaining long-term performance, many pharmaceutical industries in Nigeria struggle to embrace and effectively implement these practices in alignment with ever-changing market conditions. Therefore, the study seeks to examine the effect of product distributions strategies on the performance of pharmaceuticals in South-West Nigeria. The number of staff in some selected pharmaceutical companies was given as 3,831. Therefore, 370 respondents were taken as an adequate sample size for the study. A convenience sampling method was used. The study was driven by primary data. The data were analyzed using regression analysis as an analytical tool. The finding reveals an R2 of 0.747, which indicates a significant effect. Consequently, the study established that distribution strategies (exclusive distribution, extensive distribution, and selective distribution) influence the performance of selected Pharmaceuticals in the southwest region of Nigeria. The study concluded that pharmaceutical performance in the South-West depends on distribution strategies, exclusive distribution, extensive distribution, and selective distribution). The study therefore recommends that pharmaceutical companies in Nigeria that seek improved sales growth should adopt exclusive distribution, extensive distribution, and selective distribution to move their products to potential consumers.